Podarunek - Steel, Danielle; Wyzynski, Tomasz (Warszawa : Libros, 2001)
Polish translation of "Gift". A love story taking place in the middle west, by Danielle Steel.
Keywords: Children -- Death -- Fiction; Fate and fatalism -- Fiction; Middle West -- Fiction; United States -- Social life and customs -- 1945-1970 -- Fiction